Metal–Organic Framework Derived Copper Chalcogenides‐Carbon Composites as High‐Rate and Stable Storage Materials for Na Ions. (27th April 2022) - Li, Huihua; Zhang, Huang; Zarrabeitia, Maider; Liang, Hai‐Peng; Geiger, Dorin; Kaiser, Ute; Varzi, Alberto; Passerini, Stefano
Abstract: Transition metal chalcogenides have been regarded as promising storage materials for sodium ions owing to their high theoretical capacity. Herein, copper‐based metal–organic frameworks (Cu‐BTC) are reported as precursors to fabrica copper chalcogenides‐carbon composites, namely Cu1.8 S@C and Cu2‐ x Se@C. The materials exhibit excellent electrochemical performance with high specific capacities (504 mAh g –1 for Cu1.8 S@C and 317 mAh g –1 for Cu2‐ x Se@C at 0.1 A g –1 ) and long‐term cycling stability when used as anode materials in cells employing carbon‐coated Na3 V2 (PO4 )3 (NVP/C) positive electrodes. The Cu2‐ x Se@C||NVP/C cell delivers a specific capacity of 73 mAh g –1 at 1.2 A g –1 (based on cathode mass) and excellent cycling stability (capacity retention of 85% after 500 cycles at 0.12 A g –1 ) with Coulombic efficiency of ≈99.9%. Moreover, the Cu2‐ x Se@C composite performs well as positive electrode storage material in a sodium‐metal cell, offering a high reversible capacity of 216 mAh (per gram of Cu2‐ x Se@C) after 1800 cycles at 2 A g –1 and enabling high specific energy and power. Abstract : Cu‐based chalcogenides embedded in carbonaceous frameworks, i.e., Cu1.8 S@C and Cu2‐ x Se@C, are fabricated by MOF‐derived sulfidation and selenidation. The materials are investigated as hosts in both negative and positive electrodes in a diglyme‐based electrolyte. These materials exhibit ultrahigh rate sodium storage performance with high specific capacities and long‐term cycling stability. It is evident that copper chalcogenides are promising cathode materials for sodium metal batteries.